Antihyperglycemic And Toxicological Studies Of Ethanolic–Aqueous Extracts Of Gynura Procumbens - Algariri, Khaled Saleh (2013)
Leaves of Gynura procumbens (sambung nyawa) have been used in Malay traditional medicine among others to treat diabetes. It is understood that the leaves contain many compounds and only one or a few of these compounds possess the antidiabetic activity. Therefore, the aim of this study was to extract the leaves using solvents of different polarity, mixtures of the different ratio of ethanol-water to select the extract that contains compound(s) with the strongest antidiabetic activity and to carry out acute and subchronic toxicity tests of the extract with better activity. The antidiabetic activity of the extracts was compared based on their ability to lower down the blood-glucose level of normal rats and streptozotocin-induced diabetic rats. Dried powdered leaves of the plant were extracted with 0, 25, 50, 75 and 95% ethanol and concentrated using rotary evaporator respectively. The 0, 25, 50, 75 and 95% ethanol extracts respectively significantly reduced (p<0.005) blood-glucose level of streptozotocin induced diabetic rats at 3rd and 5th hours after oral administration of 1000 mg/kg of the extracts. The 25% ethanol extract showed the strongest antidiabetic activity and similar to metformin significantly reduced (p<0.005) blood-glucose level at the 2nd, 3rd, 5th and 7th hours after administration. In the phytochemical analysis the 75% ethanolic extract contained the highest flavonoids content, while the water extract showed the lowest value. In addition, the n-butanol fraction from 25% ethanolic extract represented the highest value of flavonoids and phenolics contents.